Kerjasama/Syirkah dalam Bisnis Islam - Maryani (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2018)
Discussion about shirkah law (cooperation / partnership) in business and the various kinds is a matter that is needed by every Muslim entrepreneur. This is to be the subject of study and to understand the code of ethics of fiqh and its practical guidance, so that it can be used well in conducting cooperation in business in this day and age.